Analysis of Instagram Messages in Drug Cases using Nist Methods - Aribowo, Eko; Dzikrianasa, Muhammad Raihandaffa (Universitas Ahmad Dahlan, 2025)
The advancement of communication technology has had a significant impact on all levels of society, particularly through the use of social media platforms such as Instagram. However, this application also has negative impacts, including its misuse by criminals to facilitate the distribution of drugs, leading to transactions where anti-forensics measures are employed by sellers during conversations. This research utilizes the National Institute of Standards and Technology (NIST) method, which consists of the steps of collection, examination, analysis, and reporting. This method is applied to identify and uncover evidence in drug transaction cases on Instagram. The researchers focus on messages between buyers and sellers, whether they have been deleted or not. The results of the study indicate that digital forensic steps using the NIST method can be applied in the process of retrieving digital evidence from the Instagram application on the smartphones of buyers and sellers. The digital forensic tools used successfully revealed relevant digital evidence on the Instagram application.